Exploring the modern Malaysian marriage: understanding the relationship of gender role attitudes, attitudes toward childbearing, family functioning and attitudes toward marriage among young adults in Malaysia - Choo May Yan,; Chloe Ng Chu Yin,; Claryce Cheong Yong Qing, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Malaysia is facing a change in the trend of marriage and family formation patterns with a significant decrease in marriage, birth and fertility rates and an increase in divorce rate over the years. Therefore, this study aims to investigate the relationship between gender role attitudes, attitudes toward childbearing, family functioning and attitudes toward marriage among Malaysian young adults. A quantitative cross-sectional study design with a purposive sampling method was conducted using an online survey. The data was collected using the General Attitudes towards Marriage Scale, Gender Role Attitudes Scale, Attitudes towards Fertility and Childbearing Scale, and McMaster Family Assessment Device – General Functioning Subscale. The online survey link was distributed on online social platforms and physically at Universiti Tunku Abdul Rahman. 100 young adults aged 18 to 25 years participated in this study. Pearson Product-Moment Correlation and simple linear regression were used to investigate the relationship between gender role attitudes, childbearing attitudes, family functioning and attitudes toward marriage. The results showed that only childbearing attitudes have a significant positive relationship and predictive effect on attitudes toward marriage. In conclusion, this finding provides insights to design interventions and awareness programs that aim to increase positive attitudes towards marriage.